A kid for two farthings - Mankowitz, Wolf 1924-1998; Frankel, Benjamin 1906-1973 (British Film Institute, 2019)
"In a lower-class London community of small shops, open-air vendors and flea-marketers, Joe, a small boy, lives with his mother, Joanne, who works in and rooms above the Kandinsky tailor shop. Joe is innocently and earnestly determined to help realize the wishes of his poor, hard-working neighbours. Hearing from Mr. Kandinsky the tale that a captured unicorn will grant any wish, Joe uses his accumulated pocket change to buy a kid with an emerging horn, believing it to be a unicorn. His subsequent efforts to make dreams come true exemplify the power of hope and will amidst hardship." [imdb.com]
Original: Großbritannien 1955
Bildformat 1.37:1
special features: presented in high definition and standard definition ; sales pitches: London street markets in archive film: archive films of Petticoat Lane and Tower Bridge Road market ; London after the war: the post-war period is evoked in archive films celebrating the city and its people ; On the ropes: a strenuous selection of archive films about wrestling and boxing ; All in a day's work: actress Vera Day recalls A kid for two farthings and 1950s film career in a new interview ; Interview with Joe Robinson (2006, 17 mins, audio only): the actor recalls A kid for two farthings in this archive interview recorded live on stage at BFI Southbank ; image gallery
Keywords: Film